Public Relations Strategy of the Agency for Pancasila Ideology Development of the Republic of Indonesia in Optimizing the Dissemination of Pancasila Values through Government Digital Media - Yoga Nathasa Amin; Megandaru Widhi Kawuryan; Frans Dione (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Digital transformation has shifted government public communication into digital channels while simultaneously placing Pancasila ideology development in a new challenge, namely how to keep national values relevant in a fast-paced, interactive space that is vulnerable to misinformation. This study aims to analyze the Public Relations strategy of the Bureau of Public Relations of the Agency for Pancasila Ideology Development (BPIP) of the Republic of Indonesia in optimizing the dissemination of Pancasila values through government digital media, as well as to identify its supporting and inhibiting factors. The study uses a qualitative approach with a descriptive-analytical design that combines deductive and inductive dimensions. The RACE model (Research–Action–Communication–Evaluation) by Cutlip, Center, and Broom (2006) is used as the main analytical framework, strengthened by Mergel’s (2013) Three Tactics of Government Social Media Adoption and Rocha’s (2014) Three-Dimensional Model of Government Website Evaluation. Data were collected through in-depth interviews with eleven informants from three groups, digital observation of Instagram @bpipri and the bpip.go.id website, and document analysis, then analyzed using source and method triangulation. The results show that the implementation of RACE is asymmetrical; the Action dimension is the most institutionalized, while Research reveals systemic gaps in audience data collection that are passive-reactive and Jakarta-centric. An event-centric paradox was also found (40–50% of content remains ceremonial), alongside a strategic strength in human-based storytelling, evidenced by Paskibraka 2025 content with an average of 19,205 likes per post and total interactions exceeding 710 million in August 2025. The main supporting factors include leadership commitment, partnerships with professional consultants, networks of Paskibraka communities and Pancasila Ambassadors, and data analytics infrastructure. The main inhibiting factors are the incompatibility between bureaucratic procedures and social media logic, limited digital communication human resources, and the absence of formal SOPs. The study recommends the formulation of digital communication SOPs, fast-track approval mechanisms, a shift in content patterns from event-centric to presence-centric approaches, and strengthening audience research through periodic active surveys.